Latest Data Regarding Device Therapy for Ventricular Arrhythmias - Vinall, Maria (MD Conference Express, 2015)
This article provides updates in the fields of device therapy for ventricular arrhythmias—including risk stratification regarding patient selection for implantable cardioverter defibrillators, the optimal programming for implantable cardioverter defibrillators to reduce inappropriate shocks, the impact of sports participation on patients with implantable cardioverter defibrillators, and the future of resynchronization therapy.